Development Of Micro Credential Design For Project Management To Improve The Quality Of Engineering Practices - Surono Surono (International Journal of Social Service and Research, 2023)
The integration of engineering practices with project management responsibilities is commonplace in the field, offering an effective solution for executing engineering projects. However, the unique discipline of project management poses a challenge, revealing a limitation in the quality of human resources with expertise in both engineering and project management. This study aims to address this gap by developing a Project Management Micro-Credential Design to formally recognize engineers possessing project management competencies. Employing the Rapid Assessment Process (RAP) integrated with the Regional Model Competency Standard (RMCS), the research outlines a comprehensive design for the development of a micro-credential in engineering project management. Key components of the design include a competency-based skill set development model, an instructional design system for quality assurance, an outcome-based learning and teaching delivery structure (OBLT), a competency-based assessment (CBA) development framework, and an operational structure for micro-credential implementation. This designed framework is adaptable for application within Professional Organizations and Professional Education of Engineers, accommodating both integrated and packaged formats, such as the Indonesian Student Micro-Credential (KMMI). The study contributes to bridging the gap in project management expertise among engineers, presenting a structured approach to enhance their competencies and recognition within the engineering profession.